Implementation of a Hip Fracture Care Pathway Using Lean Six Sigma Methodology in a Level I Trauma Center. Issue 24 (15th December 2018) - Sayeed, Zain; Anoushiravani, Afshin; El-Othmani, Mouhanad; Barinaga, Gonzalo; Sayeed, Yousuf; Cagle, Paul; Saleh, Khaled J.
Abstract : Introduction: The application of Lean Six Sigma (LSS) methodology with regard to hip fracture care remains unexamined. The aim of this study is to illustrate the application of LSS principles in the implementation of a hip fracture integrated care pathway (ICP). Methods: A multidisciplinary team at a level I trauma center formed a hip fracture ICP using LSS principles. An ICP aimed toward decreasing time to surgery to <48 hours was implemented in April 2012. Results: A total of 505 hip fracture patients met inclusion criteria. A total of 221 patients entered the preimplementation cohort, and 284 were incorporated in the postimplementation cohort. The percentage of patients who received surgical fixation beyond 48 hours significantly decreased (9.50% versus 4.23%; P = 0.01). Significantly more complications were detected in the postimplementation cohort (62.44% versus 80.10%; P < 0.01). The postimplementation cohort showed a significantly shorter length of stay ( P = 0.02) and decreased hospital cost ( P = 0.016). Conclusion: Our findings suggest that using LSS methods in an ICP at our institution resulted in markedly greater percentage of patients receiving surgical care within 48 hours, greater detection of complication, and reduced resource consumption.